CHARACTERISTICS OF COMPETITIVE ACTIVITY OF FOOTBALL PLAYERS OF VARIOUS PLAYING ROLES IN YOUTH NATIONAL TEAMS - Kalinin, E.M.; Kuzmichev, V.A.; Khomyakova, A.A.; Leksakov, A.V. (Theory and Practice of Physical Culture, 2022)
Objective of the study was to determine the characteristics of the competitive activity of players of different roles in national teams based on data received from GPS equipment. Methods and structure of the study. In the course of the work, the motor activity of highly qualified players (267 players), who are members of the Russian national sports teams, who played 95 ± 3 minutes, was studied, which was measured by the RealTrack System GPS tracking system, Spain, and then classified according to speed ranges, accelerations and decelerations. Significance of differences was determined using one-way analysis of variance in the Statistica 10.0 software. Results and conclusions. According to the results of the study, the characteristics of the motor activity of football players of various roles in the conditions of competitions, which are characterized by a certain structure of movements, were obtained. Accounting for positional requirements for competitive activity in the form of various movements is necessary when planning subsequent training sessions of various directions.